2018
DOI: 10.1016/j.tet.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Identification and synthesis of new sex-specific components of olive fruit fly (Bactrocera oleae) female rectal gland, through original Negishi reactions on supported catalysts

Abstract: Graphical AbstractIdentification and synthesis of new sex specific components of olive fruit fly (Bactrocera oleae) female rectal gland, through original Negishi reactions on supported catalysts Identification and synthesis of new sex-specific components of olive fruit fly (Bactrocera oleae) female rectal gland, through original Negishi reactions on supported catalystsIn the present study, eleven new sex-specific components extracted from female rectal gland of olive fruit flies were synthesized and identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Bioassays involving the synthetic enantiomers of oleane showed that (R)-oleane is active on males, while (S)-oleane on females, and GC analyses showed that females can produce (±)-oleane [206]. The synthesis of enantiomers of 4-hydroxyoleanes was conducted by Mori and co-workers [284] and a recent study identified and synthesised 11 new B. oleae female-specific components [285].…”
Section: Chemical Synthesismentioning
confidence: 99%
“…Bioassays involving the synthetic enantiomers of oleane showed that (R)-oleane is active on males, while (S)-oleane on females, and GC analyses showed that females can produce (±)-oleane [206]. The synthesis of enantiomers of 4-hydroxyoleanes was conducted by Mori and co-workers [284] and a recent study identified and synthesised 11 new B. oleae female-specific components [285].…”
Section: Chemical Synthesismentioning
confidence: 99%
“…Bioassays involving the synthetic enantiomers of oleane showed that ( R )-oleane is active on males, while ( S )-oleane on females, and GC analyses showed that females can produce (±)-oleane [ 207 ]. The synthesis of enantiomers of 4-hydroxyoleanes was conducted by Mori and co-workers [ 286 ] and a recent study identified and synthesised 11 new B. oleae female-specific components [ 287 ].…”
Section: Volatile Pheromonesmentioning
confidence: 99%
“…8 Today, the Sonogashira reaction is commonly performed under homogeneous catalysis conditions; 9 it does not require preformed organometallic acceptor species in stoichiometric amounts, as in the case of Negishi cross-coupling reactions, 10 which is also used for the synthesis of natural compounds. 11 For larger-scale and greener applications of the Sonogashira reaction, several methods have been developed, including copper-free reactions, solvent-less reac-tions, and, notably, Pd-based supported catalysts such as Pd/C. 12 Depending on the order of disconnection between B and C, the structure of the intermediates could change (12 or 4), even though the building blocks to obtain 8 are essentially the same; 4-tert-butyldimethylsilyl-1-iodobenzene (2), (E)-3-bromoacrylate (7) and trimethylsilylacetylene (13).…”
Section: Syn Thesismentioning
confidence: 99%
“…28,29 The reaction conditions were initially optimized using Pd EnCat TM 40 as a catalyst (Table 1), because this was already successfully tested for the synthesis of some natural compounds. 11,30 We initially tried to perform the reaction in the absence of copper (Table 1, entry 1), however, although the starting material disappeared after 3.5 h, many different side-products were formed, and a low yield of the desired product was obtained. The reaction was therefore tested under more classical Sonogashira conditions with a 2:1 ratio between palladium and copper, but with reduced catalyst loading (0.5 mol% of Pd; entries 2-4); also in this case, after 5 h, many collateral reactions took place.…”
Section: Syn Thesismentioning
confidence: 99%
See 1 more Smart Citation